2018
DOI: 10.1371/journal.pone.0193614
|View full text |Cite
|
Sign up to set email alerts
|

A common copy-number variant within SIRPB1 correlates with human Out-of-Africa migration after genetic drift correction

Abstract: Previous reports have proposed that personality may have played a role on human Out-Of-Africa migration, pinpointing some genetic variants that were positively selected in the migrating populations. In this work, we discuss the role of a common copy-number variant within the SIRPB1 gene, recently associated with impulsive behavior, in the human Out-Of-Africa migration. With the analysis of the variant distribution across forty-two different populations, we found that the SIRPB1 haplotype containing duplicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…It is known that exon 3 variable-number tandem repeat polymorphism in the dopamine D4 receptor gene ( DRD4 ) is associated with human exploratory behavior, such as novelty seeking (Munafò et al, 2008 ), and a previous study found a correlation between the distance of the macro-migration in nomadic populations and the proportion of long alleles of DRD4 , which is expected to be strongly associated with novelty seeking (Chen et al, 1999 ). A previous report also found a correlation between the migration distance and allele frequency of copy-number variants within the signal regulatory protein beta-1 (SIRPB1) gene, which is associated with impulsive behavior (Royo et al, 2018 ). Such gene polymorphisms might also be the candidate genes related to gene–gene interactions.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…It is known that exon 3 variable-number tandem repeat polymorphism in the dopamine D4 receptor gene ( DRD4 ) is associated with human exploratory behavior, such as novelty seeking (Munafò et al, 2008 ), and a previous study found a correlation between the distance of the macro-migration in nomadic populations and the proportion of long alleles of DRD4 , which is expected to be strongly associated with novelty seeking (Chen et al, 1999 ). A previous report also found a correlation between the migration distance and allele frequency of copy-number variants within the signal regulatory protein beta-1 (SIRPB1) gene, which is associated with impulsive behavior (Royo et al, 2018 ). Such gene polymorphisms might also be the candidate genes related to gene–gene interactions.…”
Section: Discussionmentioning
confidence: 96%
“…However, both males with and without haplogroup D-M55 have normal BMI; hence, the results are difficult to directly interpret with respect to survival and migration. As previous studies have suggested an association between human exploratory and impulsive behaviors, such as novelty seeking and Out-of-Africa migration (Munafò et al, 2008 ; Royo et al, 2018 ), we subsequently examined the association between haplogroup D-M55 and human motivational systems such as the aversive or behavioral inhibition system (BIS) and the appetitive or behavioral activation system (BAS). However, we did not find a significant difference in BIS/BAS scores between males with haplogroup D-M55 and non-carrier males.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, in the context of the history of out-of-Africa migration, archive data on worldwide genetic variants with frequencies such as the 1000genome project may be useful for finding new candidate genes. Indeed, by using the 1000-genome project database, Royo et al (2018) found an association between signal regulatory protein beta-1 (SIRPB1) copy-number polymorphism and the history of migration.…”
Section: Discussionmentioning
confidence: 99%